Plantar warts: Clinical insights and the Role of homeopathy in treatment - Mutreja, Kirti; Mani, Hariharan (Indian Journal of Integrative Medicine, 2026)
This case series reports both pediatric and adolescent patients with plantar and multiple cutaneous warts of varying duration, including recurrent and treatment-resistant lesions, who were treated with individualized constitutional homeopathic medicines. Remedies were selected following a comprehensive evaluation of physical, mental, and emotional symptoms, supported by repertorization. All patients demonstrated complete resolution of warts without scarring, without the use of local applications. Improvement in overall well-being was noted, and sustained long-term remission was observed, with no recurrence during follow-up periods ranging from four to ten years. These cases highlight the effectiveness of individualized homeopathic management in addressing persistent plantar warts and suggest the need for further systematic and controlled studies to evaluate its therapeutic potential.